The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3389/fnhum.2017.00389
|View full text |Cite
|
Sign up to set email alerts
|

Multisubject “Learning” for Mental Workload Classification Using Concurrent EEG, fNIRS, and Physiological Measures

Abstract: An accurate measure of mental workload level has diverse neuroergonomic applications ranging from brain computer interfacing to improving the efficiency of human operators. In this study, we integrated electroencephalogram (EEG), functional near-infrared spectroscopy (fNIRS), and physiological measures for the classification of three workload levels in an n-back working memory task. A significantly better than chance level classification was achieved by EEG-alone, fNIRS-alone, physiological alone, and EEG+fNIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 42 publications
10
55
0
Order By: Relevance
“…Brain Sci. 2020, 10, x FOR PEER REVIEW 3 of 20 respectively), a hybrid brain data incorporates more information and enabling higher mental decoding accuracy [43] confirming earlier findings [47]. Specifically, in [43] we showed that body physiological measures (heart rate and breathing) did not contribute any new information to fNIRS + EEG based classification of cognitive workload.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Brain Sci. 2020, 10, x FOR PEER REVIEW 3 of 20 respectively), a hybrid brain data incorporates more information and enabling higher mental decoding accuracy [43] confirming earlier findings [47]. Specifically, in [43] we showed that body physiological measures (heart rate and breathing) did not contribute any new information to fNIRS + EEG based classification of cognitive workload.…”
Section: Introductionsupporting
confidence: 79%
“…The measurement of neural correlates of cognitive and affective processes using concurrent EEG and fNIRS, multimodal functional neuroimaging, has seen growing interest [43][44][45][46]. As fNIRS and EEG measure complementary aspects of brain activity (hemodynamic and electrophysiological, respectively), a hybrid brain data incorporates more information and enabling higher mental decoding accuracy [43] confirming earlier findings [47]. Specifically, in [43] we showed that body physiological measures (heart rate and breathing) did not contribute any new information to fNIRS + EEG based classification of cognitive workload.…”
Section: Introductionmentioning
confidence: 99%
“…An F1 score of 0.811 was achieved when incorporating all sensor modalities. This value falls within the upper range of classification accuracies reported in domains outside of RAS, which varied from 45% to 90% [55,[87][88][89][90]. These differences may be due to experiment designs, baseline selections, and task demands.…”
Section: Fusionsupporting
confidence: 56%
“…This suggests that EEG is the most predictive modality for characterizing workload levels. Other studies in domains outside of RAS [55,[87][88][89][90] also concluded that EEG was the salient modality for workload characterization. In RAS, EEG may be especially reliable due to the design of the dVSS.…”
Section: Fusionmentioning
confidence: 93%
See 1 more Smart Citation